2022
DOI: 10.1021/acsomega.2c03388
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties and Electrocatalytic Water Splitting Activity for Precious-Metal-Adsorbed Silicene with Nonmetal Doping

Abstract: Since nonmetal (NM)-doped two-dimensional (2D) materials can effectively modulate their physical properties and chemical activities, they have received a lot of attention from researchers. Therefore, the stability, electronic properties, and electrocatalytic water splitting activity of precious-metal (PM)-adsorbed silicene doped with two NM atoms are investigated based on density functional theory (DFT) in this paper. The results show that NM doping can effectively improve the stability of PM-adsorbed silicene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…This results in localized defects and a photoactive nature and increases the formation of electron-hole recombination pairs. 155 Besides photocatalysis in recent years, it has been found by Li et al 156 that silicene doped with other precious metals can be used as an electrocatalyst in the HER and OER processes. It was found that precious metals such as Ru, Rh, and Ir promote the HER, and in its counterpart, Rh on silicene promotes OER.…”
Section: Catalysis Applicationmentioning
confidence: 99%
“…This results in localized defects and a photoactive nature and increases the formation of electron-hole recombination pairs. 155 Besides photocatalysis in recent years, it has been found by Li et al 156 that silicene doped with other precious metals can be used as an electrocatalyst in the HER and OER processes. It was found that precious metals such as Ru, Rh, and Ir promote the HER, and in its counterpart, Rh on silicene promotes OER.…”
Section: Catalysis Applicationmentioning
confidence: 99%
“…[27][28][29] Several previous theoretical reports have highlighted Si and Ge monolayers as appropriate matrices for anchoring adatoms and the resulting Si/Ge-based SACs oen exhibit distinguished catalytic performances. 18,[30][31][32] Specically, P doping can promote H 2 evolution reaction (HER) performance of both Si and Ge. 18 Fe/Ru on single-layer Ge show efficacy in removing CO contamination in H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In advancing MOFs for water splitting, various strategies have been implemented to fine-tune their structural and electronic properties for superior performance. 20,22,24,26,27 Techniques such as high-valent metal doping, vacancy creation, plasma and laser treatment, composition tuning, and ligand structure modulation have been employed to modify the electronic and structural features of MOFs, achieving remarkable activity. For instance, doping high-valent metal ions has led to significant improvements in OER activity.…”
Section: Introductionmentioning
confidence: 99%